2023
DOI: 10.30743/ll.v7i1.6786
|View full text |Cite
|
Sign up to set email alerts
|

“Osob Walikan”: Envisioning How Malangese Maintain Their Existence

Syahnidar Ravena Fadhillah,
Emy Sudarwati

Abstract: Osob Walikan, commonly referred to as Walikan Malang, can be widely used in the social life of Malang people. Developed from a code language, this language still exists even though it already served its purpose and developed into a Malang local language. This paper investigates the current perception of Malangese toward Walikan and its relationship with the maintenance of the Walikan language, which is a local code street language that has shifted to become an urban language. This qualitative study uses questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Local languages are starting to be eroded by foreign languages which are seen as more efficient to communicate with people around the world. There is another study that was just conducted [3] it was found that there are three values of Basa Walikan, the first as Malangese identity which means the participants consider it as their identity as Malangese, the second as a cultural heritage which means Basa Walikan as a part of Malang culture, and the last as a symbol of solidarity. This study also suggests that Basa Walikan has to be preserved so the language will still exist until then.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Local languages are starting to be eroded by foreign languages which are seen as more efficient to communicate with people around the world. There is another study that was just conducted [3] it was found that there are three values of Basa Walikan, the first as Malangese identity which means the participants consider it as their identity as Malangese, the second as a cultural heritage which means Basa Walikan as a part of Malang culture, and the last as a symbol of solidarity. This study also suggests that Basa Walikan has to be preserved so the language will still exist until then.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead of using aksara Jawa, Walikan Malang achieves its goals through semantic shifts and word reversals based on Javanese, Indonesian, and locally created words. According to [3] Walikan provides a mark that is exclusive to insiders, making it simple for them to be recognized both collectively and individually. The sense of intimacy that develops while utilizing this language deepens the sense of intimacy among citizens, turning it into a sign of unity.…”
Section: Slang In Malangesementioning
confidence: 99%